Book Review: E. Taniguchi, et al. City Logistics. Network Modelling and Intelligent Transport Systems - Köhler, Uwe (European Journal of Transport and Infrastructure Research, 2002)
To write a book with such a special subject as City Logistics is not an easy venture. But Taniguchi, Thompson, Yamada and van Duin succeeded to submit a scientifically sound report of this subject, where the main stress is centred on the modelling of city logistics. The book shows clearly, that freight transport and especially urban freight transport, which up to now is generally dealt by the road transport system, leads more and more to traffic problems in cities.